2011
DOI: 10.1021/jf202582t
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Bioaccessibility and Starch Digestibility for Extruded Snacks Enriched with Tomato Derivatives

Abstract: To improve the nutritional value of energy-dense extruded snacks, corn grits were replaced with tomato paste and/or tomato skin powder at ratios of 5, 10, and 20% and extruded to make expanded snack foodlike products. Using a model digestion system, lycopene bioaccessibility and uptake from the snacks into Caco-2 cells were determined. The digestibility of the starch, the main nutrient component of the snacks, was also investigated. While extrusion cooking reduced the lycopene content of the snacks, the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
12
0
3
Order By: Relevance
“…Extrusion cooking has been studied extensively to produce variety of specialty foods including pasta products and RTE breakfast cereals, baby foods, snack foods, texturised vegetable protein, pet foods, dried soups and dry beverage mixes. Extrusion not only alters digestibility of both protein and starch, both positively and negatively depending on the process variables (Singh et al ., ), but likewise affects the bioavailability / bioaccessibility of nutrients (Gu et al ., ; Brennan et al ., ; Dehghan‐Shoar et al ., ) compared with conventional cooking. There has also been a set of data examining the potential use of pre‐germinated grains (mainly rice) to enhance the nutritional content of extruded snack products.…”
Section: Extrusion Processing and Its Impact On The Nutritional Qualimentioning
confidence: 99%
See 1 more Smart Citation
“…Extrusion cooking has been studied extensively to produce variety of specialty foods including pasta products and RTE breakfast cereals, baby foods, snack foods, texturised vegetable protein, pet foods, dried soups and dry beverage mixes. Extrusion not only alters digestibility of both protein and starch, both positively and negatively depending on the process variables (Singh et al ., ), but likewise affects the bioavailability / bioaccessibility of nutrients (Gu et al ., ; Brennan et al ., ; Dehghan‐Shoar et al ., ) compared with conventional cooking. There has also been a set of data examining the potential use of pre‐germinated grains (mainly rice) to enhance the nutritional content of extruded snack products.…”
Section: Extrusion Processing and Its Impact On The Nutritional Qualimentioning
confidence: 99%
“…Similarly, Dehghan‐Shoar et al . (, ) have used lycopene‐rich fibre waste material from the tomato processing industry in the form of tomato peel from tomato paste production to increase not only the fibre content of extruded snacks but also their bioactive content. Further experiments have shown that the lycopene – fibre‐rich components can be incorporated into extruded snacks to produce novel foods rich in bioavailable lycopene (Dehghan‐Shoar et al ., ).…”
Section: Extruded Rtes and The Manipulation Of The Glycaemic Index (Gmentioning
confidence: 99%
“…The nutritional relevance of berry pomace in these foods will be evaluated by focusing on starch digestibility and polyphenols bioaccessibility using in vitro digestion and enzymatic assays [18,19,20]. The amount of bioavailable phytochemicals with antioxidant capacity depends on the digestive stability, and the release from the food matrix [21].…”
Section: The Proposed Research Agendamentioning
confidence: 99%
“…There have been several attempts to enrich food products by using pomace as a source of dietary fibre and other bioactive compounds. Dry tomato peel was used during production of meat products (Previtera et al, 2016 ), snacks (Dehghan-Shoar et al, 2010 ; Dehghan-Shoar et al, 2011 ), rye bread (Bajerska et al, 2015 ), and tomato pasta (Reboul et al, 2005 ). The physiological activity of food components such as dietary fibre, protein and phytosterols in reducing plasma cholesterol has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%